Potential Abuse of Unaccountable Management of One-Person Company in Banking Loan Agreement - Budiyono, Budiyono; Sumiyati, Yeti; Suhada, Ahmad Syauqi; Januarita, Ratna; Ali, Syuhaeda Aeni Mat (Kosmik Hukum, 2025)
One of the new legal subjects in Indonesian corporate law based on Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law (Job Creation Law) is a One-Person Company (which is then written as OPC), which is a legal entity that meets the criteria of micro and small businesses. This review aims to analyse the management mechanism of an OPC under the Job Creation Law, which is linked to the Principle of Accountability in banking credit agreements. The management mechanism of a One-Person Company under the Job Creation Law is unclear, namely the ambiguity of the definition and functions of the company's organs, which is only centered on one shareholder, concurrently as the organ that runs and supervises the company, so that the management of an OPC becomes unaccountable. The unaccountable management mechanism of an OPC has the potential to abuse the authority of the company's organs. In a banking credit agreement entered into by an OPC, this can occur at the stage of the credit application process and the execution of the credit agreement. At the credit application stage, the absence of a Board of Commissioners in an OPC has the consequence that the decision on the credit application plan is only in the hands of one organ only, namely the shareholder, who is one person, who also doubles as a director of the company through a Shareholders' Resolution. There are no other organs that can be asked for consideration and or approval related to credit applications that are in accordance with the needs of the company. Meanwhile, at the stage of implementing the credit agreement, there is no other organ that carries out the function of supervising the use of credit and the obligation to submit periodic financial reports to the bank, in accordance with the positive/affirmative covenants agreed in the credit agreement.